PENERAPAN METODE GROSS PAJAK PADA APLIKASI PENGGAJIAN BERBASIS WEB PADA UMKM KANTIN TANTE - Rizal Randy Saputra; Anjik Sukmaaji; Endra Rahmawati (LPPM Universitas Abdurrab, 2024)
Many developing UMKM require the application of technology in their business management processes. One of these UMKM is the UMKM Kantin Tante in Surabaya. This UMKM has 7 branches/stands located in several malls or shopping places in Surabaya. The payroll process for this UMKM still uses a manual process which is carried out at the end of every month by the UMKM’s owner. The payroll process starts from collecting employee data, recording attendance, calculating salaries, to printing employee pay slips. The existing process allows for errors in recording employee attendance data, difficulties in the process of searching for employee data and difficulties in making final reports or recaps. Therefore, we need an application that can help with the employee payroll process for UMKM. For application creation needs, this research utilizes the Waterfall SDLC (System Development Life Cycle) method to obtain requirements specifications and smooth the system design process. This application can make it easier for owners to manage employee data, salaries, allowances, and tax deductions. Features such as automatic salary calculation based on specified parameters, creating accurate payroll reports, and guaranteed data security, make this application a tool that can help companies optimize the payroll process. In addition, by using web technology, this application can be accessed from various devices and locations, allowing more flexible access and convenience in use. This application has been tested using BlackBox Testing with the result that all functionalities can run well. Meanwhile, for testing using SUS, the value is 77.1 where users can accept this application according to user needs.